Cover Picture: Anion Recognition by Aliphatic Helical Oligoureas (Chem. Eur. J. 44/2016). Issue 44 (30th August 2016) - Diemer, Vincent; Fischer, Lucile; Kauffmann, Brice; Guichard, Gilles
Abstract : A preorganized anion binding site at the positive end of the 2.5‐helix macrodipole. NMR titration studies revealed the ability of helical aliphatic oligourea foldamers to bind anionic guests without unfolding. The encounter between a 2.5‐helical oligourea and an anionic species is transposed on this figure to a football field with the helix as a goalkeeper and the anionic guest as the football. The positive and negative poles of the helix macrodipole are shown in blue and red respectively. More information can be found in the Full Paper by G. Guichard et al. on page15684 ff.